Dietary phytanic acid-induced changes in tissue fatty acid profiles in mice. Issue 4 (27th November 2020) - Nakanishi, Tomonori; Kagamizono, Kazuhiro; Yokoyama, Sayaka; Suzuki, Ryoji; Sakakibara, Hiroyuki; Sugamoto, Kazuhiro; Erickson, Laurie; Kawahara, Satoshi
Abstract: The aims of this research communication were to investigate the in vivo tissue accumulation of phytanic acid (PA) and any changes in the tissue fatty acid profiles in mice. Previous in vitro studies have demonstrated that PA is a milk component with the potential to cause both beneficial effects on lipid and glucose metabolism and detrimental effects on neuronal cells. However, there is limited information about its in vivo actions. In this study, mice were fed diets containing either 0.00 or 0.05% 3 RS, 7 R, 11 R -PA, which is the isomer found in milk and the human body. After 4 weeks, adipose tissue, liver and brain were harvested and their fatty acid profiles were determined by gas chromatographic analysis. The results showed that PA and its metabolite pristanic acid accumulated in the adipose tissue of PA-fed mice, and that dietary PA decreased the hepatic compositions of several saturated fatty acids such as palmitic acid while increasing the compositions of polyunsaturated fatty acids including linoleic acid and docosahexaenoic acid. However, dietary PA neither accumulated nor had a high impact on the fatty acid profile in the brain. These results suggested that dietary PA could exert its biological activities in adipose tissue and liver, although the brain is relatively less affected by dietary PA. These data provide a basis for understanding the in vivo physiological actions of PA.